Numerical investigation of a large bore, direct injection, spark ignition, hydrogen-fuelled engine. (29th May 2023) - Yosri, MohammadReza; Palulli, Rahul; Talei, Mohsen; Mortimer, Joel; Poursadegh, Farzad; Yang, Yi; Brear, Michael
Abstract: This paper presents Unsteady Reynolds Averaged Navier Stokes (URANS) simulations of a large bore, hydrogen-fuelled direct injection spark ignition (DISI) engine at different spark and start of injection (SOI) timings. Six cases are simulated, including three with various spark timings at a low boost level and three with advanced to late injection timings at a higher boost level. The numerical simulations are validated with experimental data for four out of six cases, while the other two are considered blind computational fluid dynamics (CFD) simulations. It is shown that the autoignition occurs with advanced spark timing due to high in-cylinder pressure and unburnt temperature. For different SOIs, it is demonstrated that flame propagation involves a spark-initiated flame combined with an autoignition generated flame. The case with the late injection timing features poor mixing and slower combustion due to the presence of lean mixtures near the spark plug. As a result, this case features the lowest thermal efficiency when SOI is varied. In all cases, both mixture and temperature stratification are present. Simulations of zero-dimensional chemical reactors demonstrate that this stratification must be correctly captured for accurate prediction of autoignition timing.